2020
DOI: 10.1021/acs.biomac.0c01380
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Based Polyion Complex Vesicles That Deliver Enzymes into Intact Plants To Provide Antibiotic Resistance without Genetic Modification

Abstract: Direct delivery of enzymes into intact plants using cell-penetrating peptides (CPPs) is an attractive approach for modifying plant functions without genetic modification. However, by conventional methods, it is difficult to maintain the enzyme activity for a long time because of proteolysis of the enzymes under physiological conditions. Here, we developed a novel enzyme delivery system using polyion complex vesicles (PICsomes) to protect the enzyme from proteases. We created PICsome-bearing reactive groups at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…These short peptides were conveniently synthesized by solid-phase peptide synthesis. We already reported that the 6 amino acid residues are sufficient for the formation of PICsome . Judging from the peptide length for the easy synthesis as well as the stability of the resultant vesicles, we decided the number of charged amino acid residues as 12 for both peptides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These short peptides were conveniently synthesized by solid-phase peptide synthesis. We already reported that the 6 amino acid residues are sufficient for the formation of PICsome . Judging from the peptide length for the easy synthesis as well as the stability of the resultant vesicles, we decided the number of charged amino acid residues as 12 for both peptides.…”
Section: Resultsmentioning
confidence: 99%
“…We have focused on material delivery into plants using peptide-based carriers because the direct delivery of proteins into plant cells can confer exotic functions or traits on plants without unfavorable permanent genetic modifications, which limit the practical use of plants for foods and material production. Recently, we reported that PICsome were prepared by mixing cationic and anionic oligopeptides fused with tetra­(ethylene glycol) (TEG) and that the resulting vesicles can serve as a carrier to deliver a functional enzyme, neomycin phosphotransferase II (NPTII), into plants after the modification with an appropriate cell-penetrating peptide (CPP) with a sophisticated design to penetrate the plant cell wall/membrane . The encapsulation in the peptide-based PICsome enabled NPTII to remain stable and functional for a long period in plant cells, imparting a resistance against antibiotics such as kanamycin to plants.…”
Section: Introductionmentioning
confidence: 99%
“…Covalent attachment of molecules at the compartment surface involves different chemical approaches. For example, strategies based on Cu 2+ -free click chemistry are achieved by: (i) azide–alkyne cycloaddition [ 106 , 107 , 108 , 109 , 110 ], (ii) maleimide and thiol-ene [ 111 , 112 , 113 , 114 , 115 ], and (iii) amine coupling [ 114 , 116 , 117 , 118 ]. Using a combination of strain-promoted azide–alkyne cycloaddition (SPAAC) and thiol-ene reactions, the surface modification of poly(2-methyl-2-oxazoline)- block -poly(dimethylsiloxane) (PMOXA- b -PDMS) polymersomes served to immobilize polymersomes on surfaces [ 111 , 112 , 119 ].…”
Section: Generation Of Synthetic Compartmentsmentioning
confidence: 99%
“…We studied poly(LysAibAla)3 (KAibA) and poly(LysAibGly)3 KAibG, two recently designed helical peptides incorporating Aib residues that exhibit improved biostability and internalization abilities in human and plant cells. 6,25 Moreover, widely known CPPs with distinct structures, such as helical BP100, 3,26,27 nonhelical nona-arginine (R9) 28,29 and its chiral peptide D-R9, were modeled and compared with KAibA/G (Figure 1). We used two model membranes, one composed of dipalmitoyl phosphatidylcholine (DPPC), which is commonly used to prepare liposomes for drug delivery and to investigate membrane stability and permeability in biophysical studies, 30 and a second model composed of dipalmitoyl phosphatidylcholine (DPPC), dioleoyl phosphatidylcholine (DOPC) and cholesterol (Chol) (1:1:1) (DPPC:DOPC:Chol) to more accurately model the plasma membrane (Figure 1).…”
Section: Introductionmentioning
confidence: 99%